2001
DOI: 10.1183/09031936.01.17509460
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte population and apoptosis in the lungs of smokers and their relation to emphysema

Abstract: Previously, it had been shown that T-lymphocytes are the predominant inflammatory cells found in the alveolar wall of smokers and their numbers correlated with the extent of emphysema. However, the phenotype of these cells was not defined. The aim of this study was to describe the different T-cell phenotypes and investigate the possible presence of apoptosis in the lung parenchyma of smokers.Samples from lungs were obtained at surgery from 15 patients who smoked and six who had never smoked. Samples were froze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
238
1
11

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(262 citation statements)
references
References 28 publications
12
238
1
11
Order By: Relevance
“…Despite reports suggesting a more robust association between CD8 ϩ T cells and emphysema (9)(10)(11)(12), skewing of the TCR repertoire after culture was only present in the CD4 ϩ T-cell population. Other recent reports also highlight the importance of CD4 ϩ T cells in emphysema.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Despite reports suggesting a more robust association between CD8 ϩ T cells and emphysema (9)(10)(11)(12), skewing of the TCR repertoire after culture was only present in the CD4 ϩ T-cell population. Other recent reports also highlight the importance of CD4 ϩ T cells in emphysema.…”
Section: Discussioncontrasting
confidence: 72%
“…Although the etiology of this continued inflammation is unknown, studies have shown a correlation between the number of T cells present in the emphysematous lung and disease severity (7)(8)(9)(10)(11)(12). The stimulus responsible for T-cell recruitment into the lungs of these patients remains unknown.…”
mentioning
confidence: 99%
“…Emphysema, a key component of COPD, is characterized by destruction of the airways, leading to loss of elastic recoil and decline in lung function. Epithelial and endothelial cell apoptosis in the lung is critical to the development of emphysema (38)(39)(40). Mechanisms, such as oxidative stress, are well-appreciated for their role in apoptotic cell death following smoke exposure (38,41).…”
Section: Discussionmentioning
confidence: 99%
“…Although such observations implicate T cell responses in COPD pathogenesis, the precise role of particular T cell subsets in disease progression remains ill defined. A major consequence of effector CD8 + T cell function is the apoptosis of target cells through a FasL or perforin/granzyme dependent mechanism and a number of groups have demonstrated a correlation between the levels of T cell infiltration and apoptosis related tissue destruction in the emphysematous lung (35,36). Although the nature of the CD4 + T cell response in the lungs of COPD patients is less well characterized it is accepted that in order for most classes of CD8 + T cell responses to be mounted effectively, CD4 + T cell 'help' is required.…”
Section: T Cellsmentioning
confidence: 99%